The Effects of AS160 Modulation on Fatty Acid Transporters Expression and Lipid Profile in L6 Myotubes - Agnieszka Mikłosz (Cellular Physiology and Biochemistry, 2016)
Background/Aims: AS160 is a key intracellular regulator of energy utilization in cells. It was shown to regulate GLUT4 translocation from intracellular depots to the plasma membrane, with subsequent changes in facilitated glucose uptake into the skeletal muscles. Similarly, also free fatty acids (FFAs) transmembrane transport seems to be largely protein-mediated. Therefore, the objective of this study was to examine the effects of moderate AS160 depletion (-82% mRNA, -25% of protein content) on the expression of fatty acid transporters and subsequent changes in lipid profile in L6 myotubes. Results: Surprisingly, moderate down regulation of AS160 expression was followed by increased AS160 phosphorylation (∼40%). These resulted in a greater expression of fatty acid transporters, namely FABPpm and FAT/CD36, with subsequently increased FAs cellular influx. No changes in the expression of FATP1 and 4 were noticed. Accordingly, we have observed a reduction in total TAG content. This was mainly caused by a significant changes in TAG fatty acids composition favouring a decrease in the amount of palmitic and stearic fatty acid moieties. In contrast, our experimental intervention led to distinctively increased total content of DAG and PL, but concomitantly decreased the content of all measured sphingolipids, e.g. SFA, SA1P, CER, SFO and S1P, in the AS160 knockdown group. Conclusions: Modulation of AS160 level and activity led to significant increase in the concentration of DAG and PL, which was associated with changes in FAs composition and expression of fatty acid transporters. Interestingly, the intervention also simultaneously decreased the content of sphingolipids.